Stakeholder engagement strategies, national institutions, and firm performance: A configurational perspective - Gupta, Kamini; Crilly, Donal; Greckhamer, Thomas (Strategic Management Journal, 2020)
Abstract Research summary Research documents the performance effects of attending to shareholders and treating employees well but underplays national differences in the relative power of labor and capital. We advance a configurational perspective that acknowledges the fit between stakeholder engagement, context, firm attributes and performance. As a cornerstone of this perspective, we develop a typology of stakeholder engagement strategies expressing how firms navigate the tension between conforming with local expectations—by prioritizing shareholders or employees, according to context—and being distinctive—by diverging from their peers. Analyzing a cross‐national sample of firms from 2004 to 2011, we identify combinations of engagement strategies, firm attributes, and contexts linked to high performance. Our findings highlight the multiple context‐dependent paths, which link stakeholder engagement to high firm performance. Managerial summary How do firms navigate pressures from shareholders and employees across different institutional environments? We develop a typology of stakeholder engagement strategies based on how firms in different countries strike a balance between conformity (i.e., prioritizing locally important stakeholders) and differentiation (i.e., prioritizing stakeholders that their local peers might neglect). Our findings show that the engagement strategies associated with high performance vary according to local institutional context and firm characteristics. In particular, by not merely prioritizing stakeholders who are already locally important, firms can use stakeholder engagement to differentiate themselves from their peers, and such engagement strategies are often linked to high performance.